Evaluation of Public Education and Teacher Training on the Basis of 1869 Regulation in the Ottoman Era - Kamer, Selman Tunay (Journal of History Culture and Art Research, 2020)
In the history of Turkish education, the comprehensive text regulating education was the Regulation of Public Education, which was prepared by a 13-person delegation under the leadership of Safvet Pasha under the influence of the French and published on 1 September 1869. Data sources consist of studies on the history of Turkish education and critical or explanatory works on the regulation. The regulation consists of 198 articles and addresses subjects such as teacher training and employment, determination of school levels, principles of inspection and evaluation, education management, the right to education, education allowances, and vilayet organization and examination systems. It was determined that the articles in the Regulation were not fully applied throughout the whole country, showing that not every law can be implemented throughout the whole country. This is because there may be differences in the implementation of the decisions, as there is not equality of opportunities across cities and regions.